Maslahah Mursalah sebagai Dasar Pembenaran Pencatatan Perkawinan dalam Hukum Islam dan Hukum Positif Indonesia - Dwi Runjani Juwita; Roisul Malik (Institut Agama Islam Negeri Ponorogo, 2025)
This study aims to analyze the theoretical and juridical foundations of marriage registration by examining the relevance of the concept of maslahah mursalah within the framework of the national legal system. The research employs a qualitative approach, utilizing a library research method to collect data from primary and secondary legal sources, including the Qur’an, Hadith, ushul fiqh texts, statutory regulations, and previous studies. The data were analyzed descriptively and analytically by examining the compatibility of the maqāṣid al-sharī‘ah principles in the context of marriage registration. The findings show that marriage registration can be justified syar‘i-ly because it brings public benefit (maslahah), prevents social harm (mafsadah), and strengthens legal protection for husbands, wives, and children. Furthermore, registration functions as an instrument of harmonization between Islamic law and Indonesia’s positive law. The study concludes that marriage registration represents an actualization of maslahah mursalah values in contemporary Islamic law, aligning with the objectives of sharī‘ah and the needs of modern society.